Pleckstrin-2 promotes the progression of colorectal cancer via YTHDF2-mediated TYMS mRNA stability - Zhou, Qian; Li, Yanxia; Li, Xiaomei; Zhang, Shujing; Wang, Ying; Li, Zhuoran; Wang, Xia; Li, Yuan; Li, Jingxin; Lu, Chunhua; Shen, Yuemao; Zhao, Baobing (Cellular and molecular life sciences : CMLS, 2025)
High expression of nucleotide synthetic enzyme thymidylate synthase (TYMS) is responsible for the resistance to fluorouracil (FU) treatment and worse survival in colorectal cancer (CRC). Herein, we revealed that pleckstrin-2 (PLEK2) cooperated with YTHDF2 to enhance TYMS mRNA stability in CRC via an m 6 A dependent manner . Silencing of PLEK2 led to the degradation of TYMS mRNA that suppressed DNA replication, which activated p53/p21 signaling and consequent inhibition of CRC cell proliferation via the cellular senescence. Additionally, PLEK2 is also required for CRC cell migration, invasion and stemness-like properties. PLEK2 inhibition is sufficient to ameliorate the progression of AOM/DSS-induced CRC . Together, our study identified PLEK2 as a key regulator for the progress of CRC via the regulation of TYMS expression, and demonstrated that PLEK2 is a novel therapeutic target for CRC.